Production and consumption traits and the adoption of improved maize varieties: Evidence from seed sample packs and cooking demonstrations - Van Campenhout, Bjorn; Nabwire, Leocardia; Kramer, Berber; Trachtman, Carly; Abate, Gashaw T. (International Food Policy Research Institute, 2025)
In developing countries, semi-subsistence farmers typically assume dual roles as both consumers and producers of the same crops, which shape their adoption decisions as they balance household food security with market-driven incentives. This study, conducted in eastern Uganda, employs a field experiment with two intervention arms to assess the relative importance of these factors in farmers’ decisions to adopt improved maize seed varieties. The first intervention focuses on production traits, distributing free sample packs of an improved hybrid maize variety to showcase benefits such as higher yields, pest resistance, and drought tolerance. The second intervention emphasizes consumption traits, offering cooking demonstrations and blind taste tests using flour from the same improved maize variety to highlight its taste, texture, and ease of preparation. Our findings reveal that while seed sample packs positively influenced farmers’ perceptions of both production and consumption traits, cooking demonstrations primarily affected perceptions of consumption qualities. We find some evidence that the cooking demonstrations and tasting sessions significantly boosted adoption of the improved maize seed variety promoted by the intervention. However, farmers who received seed sample packs tended to recycle the harvested grain as seed in subsequent seasons, thereby crowding out fresh seed purchases. This practice led to productivity losses, suggesting that the seed trial packs did not translate into lasting improvements in food security or increased market participation.